From Curriculum Ideals to Textbook Practice: Learner Autonomy in Indonesia’s Government-Issued EFL Textbook - Astri Winandari Berlin; Yanty Wirza (Universitas Hamzanwadi, 2026)
Promoting learner autonomy has become increasingly important in EFL education, particularly within curriculum reforms that emphasise student-centred learning, flexibility, and lifelong learning. In Indonesia, Kurikulum Merdeka positions students as active and independent learners; however, the extent to which this curricular orientation is reflected in government-issued English textbooks remains underexplored. This study examines how learner autonomy is facilitated in Work in Progress, a Grade 10 EFL textbook developed to support the implementation of Kurikulum Merdeka. Using qualitative textbook evaluation, the study analysed 73 activities from the first three chapters, including the Task, Chapter Review, Reflection, Assessment, and Enrichment sections. Nunan’s five-level framework for implementing autonomy (Awareness, Involvement, Intervention, Creation, and Transcendence) served as the analytical lens. The findings indicate that Work in Progress supports learner autonomy at four levels: Awareness, Involvement, Intervention, and Transcendence. Nevertheless, the Creation level is absent, suggesting that students are rarely positioned as designers of their own learning goals, tasks, or materials. The analysis further reveals that autonomy support is unevenly embedded across the textbook. While most core task activities emphasise awareness-building and guided learning, higher-level autonomy appears mainly in the Assessment and Enrichment sections. These findings suggest that, although the textbook reflects some principles of learner-centred curriculum reform, its facilitation of learner autonomy remains partial rather than systematic. The study highlights the need for future EFL textbook development to integrate more student-led, choice-based, and self-directed activities into core instructional sections.